INFORMATION-COMMUNICATION TECHNOLOGIES IN ADVANCED TRAINING OF MODERN TEACHER - L.M. Оliinyk (Kherson State University, 2010)
In the article the problem of application of information-communication technologies during the course of advanced training by the teachers of pre-school educational establishments and by the teachers of elementary school are analyzed. The possibilities of in-service teacher education in this process are considered.